2002
DOI: 10.1123/ijsnem.12.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Knowledge and Dietary Composition in Italian Adolescent Female Athletes and Non-athletes

Abstract: This study aims to investigate dietary composition and nutrition knowledge of 60 athlete and 59 non-athlete adolescent females (age, 14-18 years), using a 3-day food recall and a questionnaire on nutrition. The reported daily energy intake was similar in athletes and non-athletes, but less than the recommended and the estimated requirements. In the athletes, the energy supply from breakfast was higher than in the non-athletes (18.5 +/- 6.6 vs. 15.0 +/- 8.2%, p < .005). Energy intake from carbohydrates was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
5
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 0 publications
8
58
5
7
Order By: Relevance
“…Dietary westernization with easy access to ultra-processed food and lack of nutrition education could explain a poor nutritional knowledge of the adolescent swimmers. Nevertheless, our results may indicate that sport activity leads to a greater level of nutritional knowledge than in people who do not engage in physical activity [22].…”
Section: Discussioncontrasting
confidence: 44%
“…Dietary westernization with easy access to ultra-processed food and lack of nutrition education could explain a poor nutritional knowledge of the adolescent swimmers. Nevertheless, our results may indicate that sport activity leads to a greater level of nutritional knowledge than in people who do not engage in physical activity [22].…”
Section: Discussioncontrasting
confidence: 44%
“…However, both groups scored poorly (34%) compared with a criterion group of dietetic interns (76%; Barr). Three studies reported that athletes scored significantly higher on the nutrition-knowledge instrument than the comparison group (Cupisti et al, 2002;Guinard et al, 1995;Raymond-Barker et al, 2007). In one of those studies, the participants were elite, national-level athletes Note.…”
Section: Studies Comparing Athletes' Nutrition Knowledgementioning
confidence: 99%
“…Table 1 summarizes the seven articles comparing nutrition knowledge of athletes with that of a nonathlete comparison group (Barr, 1987;Collison et al, 1996;Cupisti et al, 2002;Frederick & Hawkins, 1992;Guinard et al, 1995;Raymond-Barker et al, 2007;Worme et al, 1990). Comparison-group populations varied but were mostly university or college students.…”
Section: Studies Comparing Athletes' Nutrition Knowledgementioning
confidence: 99%
“…Cupisti et al [18] studied nutritional knowledge and diet of 60 athlete and 59 non-athlete adolescents (14-18 years old) in Italy. They showed that daily energy consumed by female athletes and non-athletes was equal and lower than the recommended level in both groups.…”
Section: Discussionmentioning
confidence: 99%